(untitled) (American Journal of Multidisciplinary Research and Innovation, 2022)
Using a descriptive research methodology, this study determined parents’ levels of involvement and role construction regarding involvement in children’s reading at home. This study surveyed 379 parents of Grade 4 pupils from the Schools Division of Ilocos Norte for school year 2019-2020. The Assessment Tool on Parents’ Levels of Involvement in Children’s Reading at Home and Levels of Role Construction Regarding Involvement in Children’s Reading at Home was used to gather data. Mean was used to describe their responses to the survey-questionnaire with respect to modeling, cognitive and behavioral dimensions of parental involvement; and their levels of role construction regarding involvement in children’s reading at home. Majority of the parents had low levels of involvement in the modeling, cognitive, and behavioral dimensions; their level of role construction was high.